Estudio del fitoplancton y zooplancton en tres zonas del río Jubones - Samaniego Cobeña, Victor Hugo (2009)
This research focused on identifying qualitative and qualitative species of plankton in three areas of the Rio Jubones. The study was conducted at the mouth of the Rio Jubones Sector-Chalacal, Parish-Barbone, Guangzhou Guaba-El,-El Oro province in Planctonologia and Aquaculture Laboratory of the Faculty of Agricultural Sciences, Technical University of Machala. This investigation lasted three months, beginning in August 2008, ending in November 2008. Taking aim: to analyze and identify cuanlitativay quantitative plankton in the area of study and comparing the species that predominate in the three areas of study divided into three sectors. In the three specific areas of the Rio Jubones identified in Phytoplankton: Class Bacillariophyceae (diatoms) was found at a higher rate than another group fitoplantonico found the prevalence of 58.59% (Navicula sp, Nitzschia Brebisson and Cocinodiscus kiss iridis) Class Cianophycea followed by 29.74% and 11.76% Class Chlorophyceae; andat Zooplankton was the shellfish group with 69.66% of predominance (Copepoda Calanus, nauplii of copepods), the Group of Molluscs 2.53% Group cilia with 1.66% and 26.15% insepto larvae. While the qualitative analysis of phytoplankton which are: Zone A has 108,000 cells / ml, in Area B 266,666 cells / ml and 350,000 in Zone C, Zone C is the most productive and qualitative analysis of zooplankton found that: The Zone A 1516.67 org / lt, Zone B 2016.67 org / lt and Zone C 2916.67 org / lt, C being the most productive area. The statistical analysis of phytoplankton was taken the number of bodies found in the three areas of the Rio Jubones, indicating that the variations are different and the null hypothesis is not accepted. The three averages are significantly different. Taking these results with those found in zooplankton organisms.